Effects on thrombocytic hemostasis of a new derivate indolinone (Bangladesh Journal of Medical Science, 2019)
Objective. Specific activity of an antiplatelet drug of indolinone series (codenamed DI) was studied in vitro in a model of ADP-induced platelet aggregation in vitro and in vivo in a model of streptozotocininduced diabetes mellitus in rats.Material and Methods. Acetylsalicylic acid and dipyridamole were used as reference drugs. In vitro tests have demonstrated that DI exhibits antiplatelet activity in a wide range of concentrations (0,75×10-6 – 1.5×10-5 М, р